The Role of Christian Ethics in Corporate Leadership by Implementing the Leader Model - Shepherd - Banarto, Kris; Yosef, Hery Budi; Pasaribu, Endang (CV. Publikasi Indonesia, 2025)
Currently, the behavior of community life is experiencing a decline in ethics, they practice ethics based on what is allowed or not allowed and not based on good or bad. In the corporate environment, Christian leaders are still found who have not shown an example that they are followers of Christ. Meanwhile, Christian leaders will be observed by non-Christian employees whose leadership should have a positive impact, especially in spiritual matters. This study uses a qualitative method by analyzing data through literature studies. To find out the problems in their entirety, data sources related to Christian ethics, leadership, and information from the Bible are obtained. Christian ethics are one of the important factors for the success of Christian leaders in companies. The leader-shepherd model is a Christian leader who uses the spirit of a shepherd in practicing his leadership by seeing his employees as sheep that must be shepherded with love, attention, patience, and even leaders who are willing to sacrifice for their employees